Education Influence Using Leaflet Media on the Level of Knowledge, Compliance, and Therapy Outcomes in Prolanis Hypertension Patients at X Clinic Surakarta - Andrianto, Dita; RA Oetari; Purwidyaningrum, Ika (PT FORMOSA CENDEKIA GLOBAL, 2024)
Hypertension prevalence in Indonesia reached 34.4%. Chronic Disease Management Program or Program Pengelolaan Penyakit Kronis (PROLANIS) was one of the preventive and promotive strategies from BPJS, carried out to reduce or prevent complications of chronic diseases, including hypertension. Aim of this study was to determine education influence using leaflet media on the level of knowledge, compliance and therapy outcomes in prolanis hypertension patients at X Clinic, Surakarta. Method of this study used a quasi-experimental with pre-test and post-test design with 40 patients in each control and treatment group. Knowledge level assessed using HK-LS questionnaire, compliance assessed using MARS questionnaire, and therapy outcomes collected from medical record. The results of this study showed that education using leaflet media influenced level of knowledge with a value of p = 0.014, level of taking medication adherence with a value of p = 0.015 and results of systolic blood pressure therapy with a value of p = 0.000. There were an influence of education using leaflet media on the level of knowledge, compliance and therapy coutcome for prolanis hypertension patients at X Clinic, Surakarta.